Cost of implementing CAR-T activity and managing CAR-T patients: an exploratory study - Maria Caterina Cavallo; Marianna Cavazza; Francesca Bonifazi; Beatrice Casadei; Ilaria Cutini; Barbara Tonietti; Riccardo Saccardi; PierLuigi Zinzani; Claudio Jommi (BMC, 2024)
Abstract Background Chimeric antigen receptor T cells (CAR-T) represent an innovation but raise issues for healthcare payers because of the uncertainty on impact at market launch, high cost and important organisational impact. The literature has focused on their assessment, appraisal and market access solutions. No evidence on the costs sustained to implement CAR-T is available and a few studies reported the cost of the CAR-T clinical pathway, including the activities that are remunerated through inpatient or outpatient fee-for-service/episode. This paper aims at filling the information gap, assessing the cost of implementing CAR-T activity and the full cost of managing the CAR-T clinical pathway. Methods Cost analysis relied on the Activity Based Costing approach, which was applied to two Italian healthcare organisations, both CAR-T Centres authorized by the regional governments with a minimum of 20 patients treated with the first two CAR-T therapies launched on the market. Results The cost of implementing CAR-T was estimated at €1.31 million (calculated for one of the organizations with complete data). Most of these costs (77%) were generated by quality assurance activity. The mean cost per patient entering the CAR-T pathway (59 and 27) and surviving at follow-up (21 and 5) ranges from €48K to €57K and from €96K to €106K, respectively. Fees for hospitalization and infusion of gene therapy accounts for more than 70% of these costs. The actual hospitalisation cost varies greatly across patients and is in general lower than the fee-for-episode paid by the region to the hospital. Conclusions Despite its limitations (exploratory nature; the time spent by staff on activities which are not remunerated through fees was estimated through interviews with the CAR-T coordinators; cost items are not fully comparable), this research highlighted the relevant organisational and economic impact of CAR-T and provided important insights for policy makers and healthcare managers: the necessity to invest resources in CAR-T implementation; the need for assessing activities which are not remunerated through fees for service / episode; the opportunity to shift from fee-for-episode / service to bundled payments for CAR-T clinical pathway.